Exploring The Potential Of Herbal Plants As Natural Sunscreen Agents: Literature Review - Nadam Adi Reksa; Fania Putri Wiba Maharani; Dian Sari Anggrainy; Salwa Roihana (International Journal of Health Engineering and Technology, 2026)
Indonesia, as a tropical country, experiences high ultraviolet (UV) exposure, increasing the risk of skin damage and highlighting the importance of sunscreen use; However, chemical sunscreens may cause adverse effects, making natural ingredients promising alternatives. This study aims to evaluate the potential of herbal plants as natural sunscreens based on Sun Protection Factor (S PF) values ​​using a Systematic Literature Review (SLR) of SINTA-indexed journals published between 2021 and 2026, including experimental studies reporting in vitro and/or in vivo SPF values. The results indicate that herbal plants contain secondary metabolites such as flavonoids, phenolics, tannins, and terpenoids that contribute to photoprotective activity, with SPF values ​​ranging from minimal to ultra protection depending on plant type, extract concentration, and formulation; higher concentrations generally increase SPF, and advanced systems such as nanoemulsions improve effectiveness, although certain interactions may reduce SPF. In conclusion, herbal plants show strong potential as natural sunscreen agents; however, further formulation optimization and comprehensive safety and efficacy studies are required.